Effect of pedicle screw misplacement on the pull-out strength using personalized finite element modeling - Rouyin, A.; Nazemi, H.; Arjmand, N.; Einafshar, M.J. (Computers in biology and medicine, 2024)
Intraoperative misplacement of vertebral pedicle screws is prevalent. While a pedicle screw misplacement of up to 4 mm is often considered safe by clinical standards, this may reduce the pull-out strength thereby increasing the risk of postoperative screw loosening. This study aimed to compare the pull-out strength of ideally-placed and misplaced pedicle screws via personalized finite element (FE) modeling simulations. Three-dimensional FE models to simulate pull-out tests of pedicle screws were constructed. Vertebral geometries and material properties were both determined based on computed tomography images from lumbar spine (L1-L5) of a 29-year-old healthy male individual. Pedicle screws were bilaterally placed under four conditions: ideal placement (no cortex perforation) as well as minor medial, minor lateral, and severe lateral misplacements causing cortex perforations. Minor and severe misplacements corresponded to, respectively, grades C and D of the Gertzbein classification. After meshing and voxel-based vertebral material assignments based on two distinct mappings from literature, pull-out strengths were estimated by considering a strain-based damage model to accurately simulate bone fractures. Results indicated that the mean of FE-predicted pull-out forces for ideally-placed screws (1583 and 2412 N for material mappings 1 and 2, respectively) was within the range of previous experimental data (ranging from 1016 to 2443 N) thus confirming the model validation. The mean of all pull-out forces for each misplaced screw group was significantly smaller (p < 0.05) than that of the ideally-placed screws, e.g., 20 % for minor medial, 22 % for minor lateral, and 37 % for severe lateral misplacements. These findings indicated that even clinically-acceptable screw misplacements (up to 4 mm) could significantly reduce the pull-out strengths of pedicle screws thus imposing higher risk of postoperative screw loosening. To avoid these common screw misplacements, the use of advanced approaches for pedicle screw placements appears to be imperative. [Display omitted] •The pull-out strengths of misplaced pedicle screws were significantly smaller than those of the ideally-placed screws.•While a screw misplacement of up to 4 mm is clinically considered acceptable, it resulted in a significant reduction in pull-out force.•The ideally-placed and severe lateral misplaced screws had, respectively, the largest and smallest mean pull-out forces.•A severe lateral misplacement of pedicle screws reduced the pull-out strength by 37 %.•Unlike previous experimental tests, our study indicated that a minor medial misplacement decreases pull-out force by 20 %.